2010
DOI: 10.1016/j.limno.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two methods for estimating the abundance, diversity and habitat preference of fluvial macroinvertebrates in contrasting habitats

Abstract: a b s t r a c tIn this research we evaluate the effects of the method used for estimating the potential surface available for benthic macroinvertebrates in macrophyte and unvegetated habitats on several metrics and habitat preference of aquatic macroinvertebrates in the upper catchment of the Henares River (Guadalajara, Central Spain). Three sampling sites were selected: a well-preserved stream (site A), a stream with no wood riparian vegetation (site B), and a straightened and deforested reach (site C). Two h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Contrary to our expectations, gravel habitat supported a greater diversity of invertebrates than macrophyte habitat, and functional feeding group analysis indicated that taxa were utilizing different resources between habitats. Although a few studies have found that gravel habitat supported a higher diversity of invertebrates than macrophytes (Alonso & Camargo, ; Cogerino, Cellot, & Bournaud, ), most have concluded the opposite. Shupryt and Stelzer () found that macrophyte habitat supported a greater diversity of invertebrates than sand/gravel habitat due to enhanced habitat diversity and considered macrophyte beds as biological “hot spots.” Similarly, Strayer and Malcom () demonstrated that macrophytes were an important source of biodiversity when compared with unvegetated substrate in the Hudson River estuary.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our expectations, gravel habitat supported a greater diversity of invertebrates than macrophyte habitat, and functional feeding group analysis indicated that taxa were utilizing different resources between habitats. Although a few studies have found that gravel habitat supported a higher diversity of invertebrates than macrophytes (Alonso & Camargo, ; Cogerino, Cellot, & Bournaud, ), most have concluded the opposite. Shupryt and Stelzer () found that macrophyte habitat supported a greater diversity of invertebrates than sand/gravel habitat due to enhanced habitat diversity and considered macrophyte beds as biological “hot spots.” Similarly, Strayer and Malcom () demonstrated that macrophytes were an important source of biodiversity when compared with unvegetated substrate in the Hudson River estuary.…”
Section: Discussionmentioning
confidence: 99%
“…Separation of benthic invertebrates from extraneous organic and inorganic materials, identification and enumeration is expensive in terms of time and effort (Vlek et al, 2006). Although thorough separation of benthic invertebrate samples from extraneous materials is the only way to ensure a comprehensive characterisation of the structure of invertebrates, alternative methods that enhance analysis of samples have been developed (Santos et al, 1996;Alonso and Camargo, 2010).…”
Section: Introductionmentioning
confidence: 99%